Management of childhood diarrhea among private providers in Uttar Pradesh, India - Christa L. Fisher Walker; Sunita Taneja; Laura M. Lamberti; Amnesty Lefevre; Robert Black; Sarmila Mazumder (Edinburgh University Global Health Society, 2016)
In Uttar Pradesh (UP), India, a new initiative to introduce zinc and reinvigorate ORS for diarrhea treatment in the public and private sectors was rolled out in selected districts. We conducted an external evaluation of the program that included assessing the knowledge and practices of private sector providers 6 months after the initial program rollout.